BRANDING OF PRIVATE SCHOOLS IN FACING ZONING POLICIES - Najmy Hanifah; Istikomah Istikomah (Idaarah: Jurnal Manajemen Pendidikan, 2022)
This study aims to describe the concept of private school Branding in the face of the zoning system that has been set by the Ministry of Education, Culture, Research and Technology (Kemendikbudristek). This is because after the zoning system has been established, private schools located in the city center must compete explicitly with public schools to get new students. This type of research is a qualitative research with a phenomenological approach. Researchers will be directly involved and collect data by means of observation, interviews, and documentation In SMA Muhammadiyah 2 Sidoarjo. After that, an analysis was carried out with three stages, namely data reduction, data display, and conclusion drawing/verification. The results of the study show that private schools in the city center must struggle to get new students by developing strategies to attract the attention of students, while the Branding strategy includes brand identity, brand personality, brand positioning, and brand communication. After this strategy, especially macimizing social media promotion, the private school can compete with other private schools.